Chronic itch associated with systemic origin in patients of a multidisciplinary hospital (Russian Medical and Social Journal, 2019)
Introduction. Chronic itch is a frequent symptom of internal diseases and causes a significant decrease in the patients’ quality of life.Objectives were to study the structure of internal diseases that cause chronic itch in patients in a multidisciplinary hospital, and the features of chronic itch in these diseases; to evaluate the effectiveness of various treatment regimens for chronic itch in these diseases; to evaluate the possibility of widespread use in clinical practice of the Numeric Rating Scale for the measuring the se-verity of chronic itch in the initial diagnosis and in the determination the effectiveness of treatment.Patients and Methods. Chronic skin itching was studied in patients with various diseases undergoing inpatient treatment at the Burdenko Main Military Clinical Hospital. The study included 125 patients: 20 (16%) with chronic renal failure, 17 (13.6%) with liver diseases, 24 (19.2%) with myeloproliferative, 32 (25.6%) with lymphoproliferative and 32 (25.6%) endocrine diseases. In-dividual antipruritic therapy was selected for each patient with different systemic pathology, considering diseases that cause itching.Results. The most effective drugs in the treatment of chronic itching in patients with chronic renal failure were sorbents, gabapentin and capsaicin in the form of an ointment or cream, with cholestasis - cholestyramine, ursodeoxycholic acid, rifampicin and tacrolimus in the form of an ointment, with true polycythemia - antihistamines and mast cell inhibitors, with Hodgkin's lymphoma and mycosis fungoides - mast cell inhibitors, gabapentin and ointments with glucocorticosteroid additives, with diabetes mellitus - antihistamines, mast cell inhibitors and external therapy with calamine, menthol, capsaicin and glucocorticosteroids, with hypothyroidism - emollients. In patients with myeloproliferative and lymphoproliferative diseases and hyperthyroidism chronic itching completely disappeared only after effective treatment of the underlying disease.Conclusion. For each form of itching and for each patient individual therapy should be selected. The most effective treatment for chronic skin itching associated with systemic origin is the successful treatment of the underlying disease. The numerical rating scale is a reliable scale for measuring the severity of itching, however, it cannot consider all the complexity and features of itching.
Keywords: Chronic Pruritus; Chronic Itch; Systemic Diseases; Treatment; Numeric Rating Scale